Validation of a clinical simulation setting in the management of postpartum haemorrhage - Priscyla de Oliveira Nascimento Andrade; Sheyla Costa de Oliveira; Sheila Coelho Ramalho Vasconcelos Morais; Tatiane Gomes Guedes; Geyslane Pereira de Melo; Francisca Marcia Pereira Linhares
ABSTRACT Objective: To construct and validate a clinical simulation setting for postpartum haemorrhage. Method: Quantitative research of methodological development, carried out from May to July of 2016 with 22 expert judges and 30 students. Analysis was performed from descriptive statistics, Binomial Test and Content Validity Index (CVI), considering CVI ≥ 80%. Results: Setting construction was based on learning objectives, fidelity, evaluation tool, pre-setting activities and debriefing. Agreement, regarding its validity, was satisfactory in the 23 items analyzed. Items evaluated by judges had CVI> 0.90; in the evaluation by students, CVI was > 0.95. Conclusion: It was considered validated and suitable for training and use by nursing students. Other studies should be carried out in order to test its effectiveness in the construction of theoretical and practical knowledge of both nursing students and nurses during Permanent Education.